Control of Bacterial Leaf Blight Xanthomonas by Application of Bacillus subtilis Biobactericide on Rices - Iqbal Erdiansyah; Khusnul Khotimah (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2025)
Indonesia's agricultural problems in rice cultivation are increasingly complex, threatening national food security. The attack of Xanthomonas oryzae pv. oryzae (Xoo) can cause decreased production of bacteria, resulting in rice disease bacterial leaf blight (BLB). The biological agent Bacillus subtilis (B. Subtilis) has the potential to control BLB disease. The study aimed to determine the effect of B. subtilis bacteria in reducing the intensity of Xoo attacks by comparing the use of pesticides. Xoo attacks by comparing the use of citronella vegetable pesticide and its effect on rice production. This experiment was designed as a comparison of 2 plots with different treatments, namely the control treatment of citronella vegetable pesticide with a concentration of 75% and the biobactericide treatment of B. subtilis with an antagonistic bacterial suspension density of 33 x 104 cfu ml-1. The variables observed were inhibition, disease intensity, weight of harvested dry grain (HDG) per clump, and weight of HDG per plant. The results stated that the biobactericide B. subtilis had a real effect on the development of BLB disease up to an intensity of 14.72% and the development of BLB with citronella vegetable pesticide treatment decreased to 28.97%, the weight of HDG per clump and did not have a real effect on the weight of HDG per panicle.